IMPLEMENTASI AUGMENTED REALITY PEMBELAJARAN ORGAN TUBUH MANUSIA BERBASIS MOBILE - Hardiansah, Gian; Ardiani, Farida; Kalifia, Anna Dina (Politeknik Bisnis Indonesia, 2024)
The importance of organ learning for students at the primary and secondary education levels as a basic foundation is a crucial aspect in science and health education. However, in some schools in Indonesia, learning media still rely on conventional methods such as the use of books and anatomical models which are relatively expensive and require space. In addition, conventional media is often unable to provide an in-depth and engaging learning experience for students. This research aims to build an organ learning application utilizing augmented reality technology. The application can display human organs in 3D visual form equipped with explanations and quiz features. This research was conducted using the waterfall method starting from the problem identification stage to the testing stage. The results of the application are then tested using the blackbox testing method, where from 6 application functionalities tested show that the application runs according to the design stage.